2014
DOI: 10.1097/ajp.0b013e31829ca62f
|View full text |Cite
|
Sign up to set email alerts
|

Headache Associated With Temporomandibular Disorders Among Young Brazilian Adolescents

Abstract: HAs were a potential risk factor for TMD in adolescents, and the risk was particularly higher for painful and chronic TMD. When HAs are present in young adolescents, a complete examination is strongly recommended with regard to the presence of painful TMD, and vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 32 publications
4
33
0
1
Order By: Relevance
“…For the TMD diagnosis, the data were collected through the self‐reported questionnaire by the American Academy of Orofacial Pain (AAOP), validated for Portuguese language by Franco et al After the questionnaire, the adolescents were examined by TMD according to RDC/TMD criteria by one calibrated examiner, as described by Bertoli et al The examinations were performed at the scholarly settings in the morning or afternoon before adolescents recreation time according to the World Health Organization…”
Section: Methodsmentioning
confidence: 99%
“…For the TMD diagnosis, the data were collected through the self‐reported questionnaire by the American Academy of Orofacial Pain (AAOP), validated for Portuguese language by Franco et al After the questionnaire, the adolescents were examined by TMD according to RDC/TMD criteria by one calibrated examiner, as described by Bertoli et al The examinations were performed at the scholarly settings in the morning or afternoon before adolescents recreation time according to the World Health Organization…”
Section: Methodsmentioning
confidence: 99%
“…This can be also attributed to, at least, two more reasons. As previously commented in our recent publication 9 , the prevalence of TMD might be higher in developing countries, since low social status has comprised a risk factor for TMD pain in adults according to a recent study conducted in Brazil 18 . Moreover, the sample invitation procedure consisted of a brief explanation about TMD and its associated symptoms (e.g., headaches, joint sounds, facial pain, limitation of movements) as a requirement of the Research Ethics Committee, and it is possible that adolescents were interested in participating because they had previously noticed some of the symptoms cited by the researchers during the invitation procedure.…”
Section: Discussionmentioning
confidence: 73%
“…Question #6 is part of question #3 of the RDC/TMD 7 Axis II used as the reference standard for a positive painful TMD diagnosis, which also overlaps with other recently-developed screeners 12,21,30 . Question #7 is also presented in other screeners 29,30 and this is justified because of the strong associations reported especially between headaches 9,15,19 and neck aches 28 with TMD. Finally, question #9, about occlusal changes, probably evolved from an older proposed screener 10 and makes sense given that a recent study has demonstrated that perceived dental changes were among the most common perceived symptoms in adolescents with TMD 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In relation to this gender in particular, it was revealed that women with migraine seem to be more likely to present pain in TMD than women without headache (independent of the TMD type, whether myogenous or arthogenous) 24 . Headaches are a potential risk factor for diagnosis of chronic pain or TMD 25 . Increased headache frequency indicates higher severity of TMD 18,26 .…”
Section: Discussionmentioning
confidence: 99%